Advances in Shape Memory Materials In Commemoration of the Retirement of Professor Hisaaki Tobushi - Sun, Qingping; Matsui, Ryosuke; Takeda, Kohei; Pieczyska, Elżbieta A.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This book is devoted to the development of the shape memory materials and their applications. It covers many aspects of smart materials. It also describes the method on how we can obtain not only large recovery strains but also high recovery stress, energy storage and energy dissipation in applications. This volume treats the mechanical properties of shape memory alloys, shape memory polymers and the constitutive equations of the materials which are necessary to design the shape memory elements in applications. It also deals with the fatigue properties of materials, the method to design the shape memory elements, and the shape memory composites. The authors are international experts on shape memory alloys and shape memory polymers in the metallurgical, chemical, mechanical and engineering fields. The book will be of interest to graduate students, engineers, scientists and designers who are working in the field of electric and mechanical engineering, industries, medical engineering, aerospace engineering, robots, automatic machines, clothes and recycling for research, design and manufacturing.
1 Fabrication and output power characteristics of heat engines using tape-shaped SMA element -- 2 One-dimensional phase transformation model and its application to damping enhancement analysis -- 3 A review on experimental investigations of rate sensitivity of deformation behavior in Fe-based shape memory alloys -- 4 Shape memory effect and superelasticity of textured NiTi alloy wire -- 5 Development of the technology teaching materials using Ti-Ni shape memory alloy -- 6 A review of shape memory polymers thermos-mechanical modeling. Analysis in the frequency domain -- 7 Computational study of stretching rate effects on pattern formation in NiTi thin strips -- 8 Mechanical properties of shape memory alloys and polymers - A review on the study by Prof. Tobushi -- 9 Fatigue property and enhancement of fatigue life of TiNi shape memory alloys - An overview -- 10 Intelligent shape memory actuators -- 11 Structural and magnetic properties of magnetic shape memory alloys on Ni-Mn-Co-in self-standing films -- 12 Simultaneous measurement of continuum strain field and intermittent martensite band nucleation in single crystal Ni-Mn-Ga foils -- 13 Thermomechanical coupling and localization effects examined in shape memory alloys and polymers by fast and sensitive infrared camera -- 14 Anomalous Properties of TiNi processed by severe plastic deformation -- 15 Grain size effects on Young's modulus and hardness of nanocrystalline NiTi shape memory alloy -- 16 Grain size effects on wear resistance of nanocrystalline NiTi shape memory alloy -- 17 Experimental study of critical stresses of Fe-28Mn-6Si-5Cr SMA under various temperature conditions -- 18 Cyclic compressive responses of NiTi shape memory alloy-effects of loading frequency.
Keywords: Materials -- Analysis; Engineering design; Energy storage; Control engineering; Robotics; Automation; Characterization and Analytical Technique; Engineering Design; Mechanical and Thermal Energy Storage; Control, Robotics, Automation